Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

from Stewart, Precalculus, 5th, p56, Q. 79

Find all real solutions of the equation


my solution

$$\dfrac{x+5}{x-2}=\dfrac{5}{x+2}+\dfrac{28}{(x+2)(x-2)}$$ $$(x+2)(x+5)=5(x-2)+28$$ $$x^2+2x-8=0$$

$$\dfrac{-2\pm\sqrt{4+32}}{2}$$ $$\dfrac{-2\pm6}{2}$$ $$x=-4\text{ or }2$$

official answer at the back of the book has only one real solution of $-4$

where did I go wrong?

share|cite|improve this question
values of variable on which functions is define means function have value called as domain.If you put x=2 in your question two functions will be undefined that's why in the answer only 1 value is consider – iostream007 May 18 '13 at 17:44
The very first thing I thought when I looked at the original equation is that $2$ and $-2$ cannot be solutions. That's something to look for. And I have no doubt that what Stewart had in mind is precisely that some students would do just what you did here. – Michael Hardy May 18 '13 at 17:47
up vote 5 down vote accepted

You multiplied both sides by $(x-2)(x+2)$. If this is zero, you may introduce extra solutions, hence you need to check your final answer to see if you have any extraneous solutions. In this case, you do! For $x=2$, two of the three fractions in the original equation are undefined.

share|cite|improve this answer

Why do we have to reject the solution $x=2$?

Hint: What happens when we put $x=2$ in the original equation?
Review your equations. Make sure that you didn't multiply by 0.

share|cite|improve this answer

$$\frac{x+5}{x-2}=\frac{5}{x+2}+\frac{28}{x^2-4}$$ multiply both sides with $(x-2)(x+2)\neq 0$ or $x\neq 2,x\neq -2$ we get $$(x+5)(x+2)=5(x-2)+28,x\neq 2,-2$$

$$x^2+2x-8=0,x\neq 2,-2$$

$$x^2-2x+4x-8=0,x\neq 2,-2$$ $$x(x-2)+4(x-2)=0,x\neq 2,-2$$ $$(x-2)(x+4)=0,x\neq 2,-2$$ so $x+4=0$ or $x=-4\neq 2,-2$ is unique solution because from $x-2=0$ follow solution $x=-2$ that is prohibited

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.